Algunos comentarios a las consecuencias tributarias derivadas del secondment transfronterizo de personal - López Saldaña, Cesar (Pontificia Universidad Católica del Perú, 2016)
The objective of this article is to analyze, from a tax perspective some aspects arising from the secondment, such as the possible double residence of the employees assigned, the application of income tax on income from personal servicedependent on light model Convention for the Avoidance of Double Taxation of the Organization for Economic Cooperation and Development (“OECD CDI”) and the possible establishment of a permanent establishment by assigning employees to the State of destination.

El objetivo del presente artículo es analizar, desde un punto de vista tributario, algunos aspectos derivados del secondment, tales como la posible doble residencia de los empleados asignados, la aplicación del Impuesto a la Renta sobre los ingresos derivados del servicio personal dependiente a la luz del Modelo del Convenio para Evitar la Doble Imposición de la Organización para la Cooperación y Desarrollo Económico (“CDI OCDE”) y la posible constitución de un establecimiento permanente por la asignación de empleados al Estado de destino.
Some comments to the tax consequences arising from cross-border secondment of staff
Keywords: Secondment; Tax; Income Tax; Double Residence; Allocation Of Employees; Secondment; Tributario; Impuesto A la Renta; Doble Residencia; Asignación de Empleados; https://purl.org/pe-repo/ocde/ford#5.05.00